A New Diaphragm Wall Technology Providing Mechanical And Watertightenss Continuity - P. Dupeuble (Deep Foundations Institute, 2010)
Diaphragm walls, owing to their method of construction are discontinuous structures. A new technology for the construction of joints between panels has been developed. This new process allows for the construction of diaphragm walls with mechanical and watertight continuity.